On a new generalization of a Perov-type F-contraction with application to a semilinear operator system - Muhammad Sarwar; Syed Khayyam Shah; Kamaleldin Abodayeh; Arshad Khan; Ishak Altun (Fixed Point Theory and Algorithms for Sciences and Engineering, 2024)
Abstract This manuscript aims to present new results about the generalized F-contraction of Hardy–Rogers-type mappings in a complete vector-valued metric space, and to demonstrate the fixed-point theorems for single and pairs of generalized F-contractions of Hardy–Rogers-type mappings. The established results represent a significant development of numerous previously published findings and results in the existing body of literature. Furthermore, to ensure the practicality and effectiveness of our findings across other fields, we provide an application that demonstrates a unique solution for the semilinear operator system within the Banach space.